Impact of Economic Sanctions on Bilateral Trade Relations: A Comparative Study of US Sanctions on Iran and North Korea - Cheo, Joe (American Journal of International Relations, 2024)
Purpose: The aim of the study was to assess the impact of economic sanctions on bilateral trade relations, a comparative study of US sanctions on Iran and North Korea. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed significant disruptions in trade dynamics between the United States and the targeted nations. The sanctions often lead to a substantial decrease in bilateral trade volumes, with affected countries experiencing reduced exports to and imports from the U.S. This decline is primarily due to the increased costs and risks associated with trading under sanctions, which deter businesses from engaging in commercial activities. Furthermore, the study highlights that the effectiveness and impact of sanctions vary depending on the economic resilience and trade diversification of the targeted country. Nations with diversified trade portfolios and stronger economic ties with non-U.S. partners are better able to mitigate the adverse effects of sanctions. Conversely, countries heavily reliant on U.S. trade face more pronounced economic hardships. The study underscores the strategic use of sanctions as a tool of foreign policy, illustrating both their intended and unintended economic consequences on global trade relations. Implications to Theory, Practice and Policy: Deterrence theory, economic statecraft theory and interdependence theory may be used to anchor future studies on assessing the impact of economic sanctions on bilateral trade relations, a comparative study of US sanctions on Iran and North Korea. In practice, policymakers should adopt a more targeted approach in designing economic sanctions. Policymakers should prioritize international collaboration and coordination to ensure that sanctions achieve their intended political objectives without exacerbating humanitarian crises.